Pasting Properties of Mocaf (Modified Cassava Flour) Using Rapid Visco Analyzer With Variations of pH Solution - Nia Ariani Putri; Achmad Subagio; Nurud Diniyah (University of Sultan Ageng Tirtayasa, 2022)
Starch is a glucose polysaccharide which includes amylose and amylopectin. Natural starch in its utilization has several weaknesses so that modified starch begins to develop, one of which is MOCAF. MOCAF is a modified cassava flour by fermentation using lactic acid bacteria (BAL). The weakness of natural starch is become thicky when the food processing at high temperature and acidic conditions. MOCAF is expected to be able to provide solutions for food processing at high temperatures and acidic conditions. This research was conducted to determine the gelatinization profile of MOCAF during processing at several pH levels. Physical properties of the MOCAF firstly were analyzed including water, starch, amylose, and amylopectin content. After that, the MOCAF gelatinization profile was measured using a Rapid Visco Analyzer (RVA), with observation parameters namely peak viscosity (PV), minimum viscosity (MV), breakdown (BD), final viscosity (FV), setback (SB), pasting temperature (PT), and peak time (Ptime). The results showed that the acidic conditions affected the gelatinization profile of the starch. In the sample which was mixed with citrate buffer solution pH 3 showed the highest peak viscosity (4206.4 cP) and breakdown (3047.6 cP), while the lowest minimum viscosity (1158.6 cP), final viscosity (1604.0 cP), setback (445.2 cP), pasting temperature (74.28°C), and peak time (4.31 minutes). Thus, the low-pH processed MOCAF has the lowest viscosity stability and retrogradability.